Incidence of maxillofacial fractures in motor vehicle accidents treated in Dubai - Sam Thomas Kuriadom; Sahrash Dar; Faranak Saffari; Mohamed Jaber (Saudi Dental Journal)
Aims: To analyze the incidence of maxillofacial fractures due to motor vehicle accidents in Dubai, as well as age, sex, etiology, patterns, treatment, and complications. To compare the findings with similar studies and provide recommendations for the prevention and management of these fractures. Materials and methods: A 7-year retrospective study of maxillofacial fractures due to motor vehicle accidents was done. Results: We found that most of the accidents took place in December, and the majority of the patients were pedestrians (27%). Male to female ratio was 6:1, and patients in their third decade of life were the most affected (39%). The parasymphysis was the most prominently affected region (27.7%), followed by the orbital bone (18.6%). Open reduction surgery was done in 56% of the cases, and postoperative complications were found in 18.4%. Conclusions: Pedestrians were most commonly involved in the accidents. An increase in awareness, trauma centers, and better facilities would perhaps improve the management of such fractures.